OP0175 Systemic Lupus Erythematosous and Primary Sjogren's Syndrome May Display Joint Erosions on MRI as Well as Healthy Control, but Cannot be Considered as Erosive Disease Such as Rheumatoid Arthritis: An MRI Observational Study of 90 Subjects. (23rd January 2014) - Gandjbakhch, F.; Foltz, V.; Renoux, J.; Costedoat, N.; SENE, D.; Mercy, G.; Amoura, Z.; Piette, J. C.; Morel, N.; Cozic, N.; Bourgeois, P.; Fautrel, B.
Abstract : Background: Recent studies tend to demonstrate presence of MRI erosion in Systemic Lupus Erythematosous (SLE) and primary Sjogren's syndrome (pSS). Better knowledge of erosions' characteristics of these different diseases may improve MRI interpretation. Objectives: To describe MRI characteristics (erosion and osteitis) of patients with SLE and pSS compared to "positive control", i.e. RA and "negative control" (sex/age- matched healthy controls ). Methods: pSS, SLE, RA patients and HC were prospectively included from 2 departments (rheumatology and internal medicine) between 2009 and 2011. Inclusion criteria were: 1- for SLE and pSS : disease duration >2 years, no association with RA, i.e. no arthritis, no ACPA, normal X rays of hand and feet. 2-for Healthy controls (HC): no history of tender/swollen joint or rheumatic disease. 3- for RA: established RA, i.e. duration>2 years. MRI of MCP2 to 5 and wrist of the dominant hand was performed using a dedicated MRI (ESAOTE Cscan 0.2 Tesla) in coronal and axial plans using T1 and STIR sequences, without gadolinium injection, to evaluate erosion and osteitis according to the OMERACT definitions. Erosion was defined as an intra-articular cortical break visible in two planes (OMERACT definition), not related to vascular foramen or ligament insertion.2 independent readers evaluated MRI, blindly to clinical and radiographic data, using RAMRIS scores for erosion and osteitis. Statistics were performed using SAS 9.3 software. Results: 90 subjects were included prospectively: 19 pSS, 21 SLE, 30 RA and 20 HC.Mean age was respectively 38.8±9.8, 54.4 ±14.2, 53.9±13.1, 42.7±11 years for SLE, pSS, RA patients and HC. 83% of RA patients were erosive on Xrays, 86% and 72% were RF and ACPA positive. All SLE and pSS patients had normal Xrays (inclusion criteria). Cortical break were seen in all groups without statistical difference. Frequencies and scores for erosion and osteitis were statistically different between RA and SLE/pSS while no statistical difference was seen between SLE/pSS and HC (Table). Sensitivity and specificity were respectively for erosion: 0.93 and 0.38, for erosion with grade ≥2: 0.4 and 0.88 and for osteitis: 0.77 and 0.78. Conclusions: MRI Cortical break are frequent in SLE and pSS as well as in HC. Erosion may occur in SLE and pSS but erosion of grade≥2 and osteitis are highly specific of RA. Distinction of physiological cortical break and pathological erosion may lead to better interpretation of MRI. Disclosure of Interest: None Declared